Foodsaving in Europe : At the Crossroad of Social Innovation - Baglioni, Simone; Calò, Francesca; Garrone, Paola; Molteni, Mario (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This book provides comparative, multi-disciplinary research on the surplus food distribution in Europe and its relation to food poverty, with a focus on the interaction of for-profit and non-profit organisations. It offers an informed and rich discussion in understanding the collaboration between profit and non-profit organisations involved in food recovery dynamics, and provides understanding as to how the two types of players create effective, innovative and sustainable processes. Building on sociology, food justice, and sustainable management fields, the book will be of interest to a diverse range of scholars, policy makers and practitioners inspiring innovation in how to address food poverty through surplus food recovery.